Sweet pepper (Capsicum annuum) grown under greenhouse conditions: correlations among variables (Revista Posgrado y Sociedad, 2020)
For 27 sweet pepper genotypes (including conical, square and rectangular fruit shape) grown under greenhouse conditions the researchers estimated Pearson correlations among twelve quantitative variables, to know the association between these characters: plant height (m), leaf area (cm2), stem diameter (mm), stem length (cm), fruit width (cm), fruit length (cm), fruit wall thickness (mm), number of first quality fruits per plant, number of total fruits per plant, number of days to the start of harvest (days after transplant), first quality fruit weight (g), and commercial yield (ton/ha). The crop was planted on coconut fiber as substrate, and managed with fertigation and Spanish pruning method. Among the 27 evaluated genotypes there were 15 Pearson correlations that were high (r≥0,69) and statistically significant (p≤0,05). In those cases the linear regression statistic were calculated. Statistically significant correlations were also observed in six additional cases, not across all genotypes but estimated according to the type of pepper (conical or square). It is concluded that the sweet pepper type included in the analysis has a large effect in the correlation results.
Keywords: Capsicum annuum, quality, yield, Pearson correlation, linear regression.; capsicum annuum; calidad; rendimiento; correlación de Pearson; regresión lineal